161 Impact of right ventricular dysfunction on outcome in heart failure patients with mid-range ejection fraction with and without chronic respiratory diseases. (17th January 2020) - Liu, D; Hu, K; Scheffold, C; Liebner, F; Kirch, M; Lengenfelder, B; Ertl, G; Frantz, S; Nordbeck, P
Abstract: Background: The impact of right ventricular (RV) dysfunction on outcome of heart failure patients with mid-range left ventricular ejection fraction (HFmrEF, 40-49%) is not well characterized yet. In this study, we observed the association between echocardiography defined RV dysfunction with outcomes and if the outcome was jointly affected by co-existed chronic respiratory diseases (CRD: asthma, chronic obstructive pulmonary disease, occupational lung diseases, sleep apnea syndrome) in HFmrEF patients Methods: 1090 HFmrEF patients referred to our department between 2009 and 2017 were included in this study. Baseline demographic and clinical data were obtained by reviewing the medical records. All patients subsequently completed a median clinical follow-up of 26 (15-38) months. The primary endpoint was all-cause mortality or heart transplantation (HTx). Right heart morphology and function were assessed with the use of multiple echocardiographic parameters, including right atrial area (RAA), RV mid diameter (RVD), tricuspid annular plane systolic excursion (TAPSE) and systolic pulmonary artery pressure (sPAP). Results: Mean age was 69 ± 13 years and 73.4% were male. The proportion of NYHA functional class III or IV was 24.8%. CRD was identified in 209 (19.2%) patients. 280 patients (25.7%, without CRD: 204, with CRD: 76) died and 2 patients (without CRD) underwent HTx. All-cause mortality/HTx was significantly higher in HFmrEF patients with CRD than without CRD (36.4% vs. 23.4%, P < 0.001). Besides CRD, Cox regression analysis showed that age, body mass index, and cardiac risk factors and comorbidities including diabetes, atrial fibrillation, dyslipidemia, coronary artery disease, kidney dysfunction (eGFR <60ml/min/1.73qm), anemia were associated with increased all-cause mortality/HTx (all P < 0.05). Multivariable Cox regression models showed that sPAP (HR 1.015, P = 0.002) and TAPSE (HR 0.962, P = 0.004) were independent determinants of all-cause mortality/HTx in patients without CRD, while sPAP served as independent determinant of all-cause mortality/HTx In patients with CRD (HR 1.018, P = 0.026) after adjusted for above mentioned confounders. Patients without CRDs were further grouped into those with normal (sPAP ≤ 40mmHg and TAPSE≥14mm, n = 513); mild to moderate (sPAP > 40mmHg or TAPSE < 14mm, n = 387) and severe RV dysfunction (sPAP > 40mmHg and TAPSE < 14mm, n = 88). Severe RV dysfunction was independently associated with a 2-fold increased all-cause mortality/HTx as compared to normal RV function (HR 2.209, 95% CI 1.455-3.355, P < 0.001). Conclusions: Increased sPAP and reduced TAPSE are independent determinants of all-cause mortality in HFmrEF patients without CRD, and sPAP is an independent determinant of all-cause mortality in HFmrEF patients with CRD. Moreover, HFmrEF patients with severe RV dysfunction face a 2-fold increased all-cause mortality, as compared to patients with normal RV function and no CRD.